A New Method of the Logical Functions Minimization in the Polynomial Set-Theoretical Format. 3. Minimization of Function System - Rytsar, B.Ye. (Управляющие системы и машины, 2015)
A new minimization method of the logic functions system of n variables in polynomial set-theoretical format is considered. The method is based on the splitting procedure of minterms system and on the generalizing the conjuncterms set of the different ranks by the settheoretical simplifing rules. The advantages of the suggested method are illustrated by the examples.